Ambientalização curricular na educação infantil : um diálogo possível a partir das relações com a natureza, o afeto e o cuidado - Zeglin, Irene Vonsovicz (2016)
This research in a master¿s degree level, had as an objective to analyze if the Curricular Orientations for the Child Education in the Municipal Network (FLORIANÓPOLIS, 2012) in theCenter of Pedagogical Action of the Relations with the Nature and the National Curricular Guidelines for the Child Education (BRASIL, 2009a) present evidence and aids that collaborate with the curricular environmentalization process and consider the affection relationship and caring as essential to the forming process of the Child Education. The research, of qualitative, exploratory and documental matter, comprehended an analysis of the mentioned documents. The bibliographical uprising (literature) considered the theoretical assumption of the environmentalization theme. Twenty key-expressions that can signalize the existence of evidence and aids of an environmentalized curriculum: Social/Society, Sustain/Sustainability, social-environmental, ecology/ecologic, nature/natural (FIGUEIREDO; GUERRA, 2014) and others defined by this research (Environment Education, Environment, natural environment, biodiversity, environment sustainability, sustainability development, water, energy, consume, residue/trash, care, affection, tenderness, human values and love)were used. The searching for these key-expressions, in both documents, happened according to a generated file in a researchable Portable Document Format (PDF), using the ¿search¿ tool (SANTOS; FERREIRA, 2015). The reflection throughout the findings happened correlating with the researches in the area. Among the results, it was observed that, in the National Curricular Guidelines for the Child Education, from the twenty key-expressions researched, seven have been contemplated. Whereas, in the Curricular Orientations for the Child Education at the Municipal Network of Florianópolis, specifically at the Center of Pedagogical Action of the Relations with the Nature and the National Curricular Guidelines for the Child Education, twelve key-expressions have been contemplated. It is suitable to reinforce that the contexts of the key-expressions remind partially the evidence and aids to an environmentalized curriculum. Although the information found does not reflect a reality of a consolidated environmentalization process, it shows some possibilities in that way. It is important to emphasize that the simple occurrence of the key-expressions in the body of the studied documents does not necessarily mean that the curricular environmentalization have been fully incorporated, but may indicate some preoccupation in treating/incorporating the reflection/discussion of the aspects of the environmental problematic in this significant stage of the Basic Education. This research did not have as an objective to evaluate the documents, neither to attribute them a value judgment. It is believed that both documents may contemplate even more the relating aspects to the environmentalization and to the dimensions of the affection and caring in the Child Education. The tests done in this research, as aids to the Child Education, came from some adaptations of related authors. An environmentalized curriculum, in the conception of this research, must predict/propitiate that the unities of Child Education establish a more balanced and sustained relation with the environment; To commit with a formation founded in the affection and caring, organizing the institutions to be examples to the children and to the community . The educational environment, when applying approaches committed to the environmentalization and under the affection and caring, has the opportunity of becoming a reference to its community and to contribute to the formation of sensitive, affectionate, responsible, ethic citizens that are willing to assume a commitment with the social-environmental sustainability in all its nuances and dimensions.